Gender and resilience to health shocks: Evidence from financial and health diaries in rural Kenya and Nigeria - Janssens, Wendy; Kramer, Berber; Murphy, Mike (International Food Policy Research Institute, 2019)
Health shocks (unpredictable illnesses and injuries) are an important source of risk for individuals in developing countries. In the absence of formal financial products such as health insurance or health savings accounts, unexpected illness or injury can have severe consequences. The burden of responding to health shocks often falls disproportionately on women, since they usually act as primary caregivers in households, and as a result are responsible for managing the health of children or elderly dependents. Despite this, much research around the uptake of health insurance or other risk-management products focuses on households instead of individuals, without considering how gender may affect individual preferences for, and access to, these products. To address this issue, this policy brief uses a unique dataset on individuals from rural households in sub-Saharan Africa to demonstrate how the financial lives of men and women differ in important respects, and how these differences may have important implications for policy on universal access to health services.